+0  
 
+1
139
2
avatar+2448 

Please help asap

 Sep 6, 2018
 #1
avatar+98197 
+2

10 )  21k^3  + 18k^2  + 56k + 48

GCF  of 21k^3  and 18k^2 = 3k^2

GCF of 56k and 48  = 8

So we have

3k^2 ( 7k + 6) + 8 (7k + 6)  =

(7k + 6) (3k^2 + 8)

 

11) 42x^3  + 49x^2 - 36x - 42

GCF of 42x^3 and 49x^2  = 7x^2

GCF of  -36x and -42  = -6

So we have

7x^2 ( 6x + 7)  - 6(6x +7)  =

(6x + 7)(7x^2 - 6 )

 

12)  p^3 + 6p^2 - 3p - 18

GCF of  p^3  and 6p^2 =  p^2

GCF of -3p  and  - 18  = -3

So we have

p^2 ( p + 6)  - 3(p + 6)  =

(p + 6) ( p^2 - 3 )

 

 

cool cool cool

 Sep 6, 2018
 #2
avatar+2448 
+1

Thank you so so so so soooo much!!laugh

RainbowPanda  Sep 6, 2018

32 Online Users

avatar
avatar
avatar